Vectorial phase retrieval for linear characterization of attosecond pulses - Raz, O; Schwartz, O; Austin, D; Wyatt, A; Schiavi, A; Smirnova, O; Nadler, B; Walmsley, I; Oron, D; Dudovich, N (2011)
We propose a new linear and all-optical method for attosecond pulses characteri-zation. Our scheme is based only on spectral and polarization measurements. We demonstrate this method numerically on attosecond pulses generated from aligned CO2 molecules. © 2011 Optical Society of America.